Mathematical model and experimental characterization of vertically stacked capacitive tactile sensors - Baldini, G; Staiano, M; Grella, F; Frascio, M; Maiolino, P; Cannata, G (IEEE, 2023)
Capacitive sensors are widely used in robotics for their compactness, high resolution, high sensitivity, and large dynamic range. In this article, we present a design solution for the manufacturing of capacitive tactile sensors with enhanced dynamic range and sensitivity. Herein, we adopted the approach of exploiting the vertical direction of the sensors by creating stacks of capacitors. The validation of the proposed model is conducted by means of finite element simulations and the effectiveness of stacked capacitors in suboptimal configurations has been experimentally tested by using inkjet printing and spin coating-based fabrication techniques. Results show that these sensors exhibit an enhanced dynamic range and sensitivity with respect to common single capacitors, for a given sensors area budget. Sensitivity increases of 235% passing from one-stack to two-stack capacitors (from 5.75 to 19.3 fF/kPa) and a growth of 23% from two-stack to three-stack capacitors (from 19.3 to 23.7 fF/kPa). These results suggest that the proposed methodology could be adopted for designing tactile sensors with higher spatial resolution and higher transduction sensitivity and dynamic range, in the perspective of an integration over large areas.